Rising incidence of early‐onset colorectal cancer in Australia over two decades: Report and review. Issue 1 (January 2015) - Young, Joanne P; Win, Aung Ko; Rosty, Christophe; Flight, Ingrid; Roder, David; Young, Graeme P; Frank, Oliver; Suthers, Graeme K; Hewett, Peter J; Ruszkiewicz, Andrew; Hauben, Ehud; Adelstein, Barbara‐Ann; et al.
Abstract The average age at diagnosis for colorectal cancer (CRC) in Australia is 69, and the age‐specific incidence rises rapidly after age 50 years. The incidence has stabilized or is declining in older age groups in Australia during recent decades, possibly related to the increased uptake of screening and high‐risk surveillance. In the same time frame, a rising incidence of CRC in younger adults has been well‐documented in the United States. This rise in incidence in the young has not been reported from other countries that share long‐term exposure to westernised urban lifestyles. Using data from the Australian Institute of Health and Welfare, we examined trends in national incidence rates for CRC under age 50 years and observed that rates in people under age 40 years have been rising for the last two decades. We further performed a review of the literature regarding CRC in young adults to outline the extent of current understanding, explore potential risk factors such as obesity, alcohol, and sedentary lifestyles, and to identify the questions remaining to be addressed. Although absolute numbers might not justify a population screening approach, the dispersal of young adults with CRC across the primary health‐care system decreases probability of their recognition. Patient and physician awareness, aided by stool and emerging blood‐screening tests and risk profiling tools, have the potential to aid in identification of those young adults who would most benefit from a colonoscopy through early detection of CRCs or by removal of advanced polyps.